2019
DOI: 10.1016/j.jses.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of patient-specific instrumentation in shoulder arthroplasty: a systematic review and meta-analysis

Abstract: BackgroundThere has been significant recent emphasis on the use of patient-specific instrumentation (PSI) in shoulder arthroplasty. However, clinical data are lacking to support the increased time and expense associated with PSI. Our purposes were to determine whether PSI significantly improves implantation accuracy during total shoulder arthroplasty (TSA) and to analyze available techniques and correlation with clinical outcomes. We hypothesized that PSI may improve glenoid component position radiographically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 43 publications
(146 reference statements)
1
36
1
Order By: Relevance
“…Our lab results in this proof-of-concept study compare favourably with published data in conventional surgery [ 17 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our lab results in this proof-of-concept study compare favourably with published data in conventional surgery [ 17 ].…”
Section: Discussionsupporting
confidence: 84%
“…Our results cannot be compared directly to studies using PSI for shoulder arthroplasty, but the reported mean postoperative version and inclination errors of 5 • or less compared with preoperative plans [17,18] are equal to our results, which were obtained simply using a see-through device (HoloLens 2). This finding suggests that AR-based aid can be particularly advantageous for novice or low-volume shoulder surgeons.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Our intervention group (group 1) had a plan that the surgeon used specifically to guide implant selection while operating; it was followed and utilized during surgery, whereas the control group had a plan that was reviewed; however, the surgeon did not use it to guide and restrict the trays or implants that were brought into the OR. All patients underwent a preoperative plan as a standard of care for this surgeon and patients in group 1 were collected from 2018 to 2020; given the published accuracy of 3D templating software 1 , 2 , 3 , 4 , 11 , 12 , 13 to guide addressing pathology and implant selection, the surgeons changed their practice to base the intraoperative plan and implant selection off of the preoperative planning software selections. This practice evolution was applied for all shoulder arthroplasty patients to minimize any bias in patient selection.…”
Section: Methodsmentioning
confidence: 99%
“… 28 Although limited studies have demonstrated reduced costs for templating software and template-directed instrumentation for total knee replacement, 13 studies have not shown the same cost-effectiveness of using patient-specific instrumentation shoulder arthroplasty procedures. 2 The purpose of our study is to assess how preoperative planning in SA could impact surgical efficiency and intraoperative costs. We hypothesize that, given the accuracy of preoperative planning, it can lead to decreased costs and increased efficiency in the operating room for SA.…”
mentioning
confidence: 99%